2021
DOI: 10.1111/iju.14596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of androgen deprivation therapy on cognitive functioning in men with prostate cancer: A systematic review

Abstract: The objective of this study was to review publications assessing cognitive functioning in patients with prostate cancer treated with androgen deprivation therapy. We conducted a systematic review of the literature published in PubMed, Embase, Web of Science, Cochrane Library, and PsycINFO up to February 2020. A total of 31 studies were included. Half of the studies (n = 16) demonstrated that androgen deprivation therapy in patients with prostate carcinoma did not result in a negative effect on cognitive functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…A systematic review and meta-analysis of 14 studies with 417 patients with prostate cancer treated with ADT, associated ADT with worse performance on visuomotor tasks, but not other cognitive domains, compared to noncancer control groups [ 78 ]. A recent systematic review of 31 studies found that 16 did not show a negative effect of ADT on cognition, whereas 11 studies reported a negative effect on cognitive function and 4 were inconclusive [ 79 ]. Therefore, ADT may have adverse effects on cognitive performance, but this is not invariable and may be limited to specific domains.…”
Section: Studies Of Men Undergoing Androgen Deprivation Therapy For P...mentioning
confidence: 99%
“…A systematic review and meta-analysis of 14 studies with 417 patients with prostate cancer treated with ADT, associated ADT with worse performance on visuomotor tasks, but not other cognitive domains, compared to noncancer control groups [ 78 ]. A recent systematic review of 31 studies found that 16 did not show a negative effect of ADT on cognition, whereas 11 studies reported a negative effect on cognitive function and 4 were inconclusive [ 79 ]. Therefore, ADT may have adverse effects on cognitive performance, but this is not invariable and may be limited to specific domains.…”
Section: Studies Of Men Undergoing Androgen Deprivation Therapy For P...mentioning
confidence: 99%
“…In four studies, the results were inconclusive. The authors also noted that future research should focus on further exploring brain features with functional magnetic resonance imaging because this technique may be more sensitive in detecting brain abnormalities in patients treated with ADT [46]. Neuroimaging studies indicate that ADT may cause changes in regional brain metabolism associated with alterations in spatial performance and VM.…”
Section: Testosteronementioning
confidence: 99%
“…While the benefits of androgen deprivation therapy (ADT) have been well established for prostate cancer (PC) patients, it is also known to cause various adverse events as a consequence of testosterone deficiency 1 . Recently, there has been growing interest in the association between ADT and cognitive function, but no consensus has yet been reached 2 . Androgen receptors are highly expressed in the prefrontal cortex and hippocampus in the brain cortices and these regions are considered to responsible for memory and higher order cognitive functions 3 .…”
Section: Introductionmentioning
confidence: 99%